Absorption Kinetics of Sulfur Dioxide in Flint Corn during Steeping - Haros, C. M. (2001)
A mathematical model was proposed to simulate simultaneous sulfur dioxide absorption and reaction during corn steeping. The parameters of the model, the diffusion coefficient and the reaction rate constant, were determined. The reaction rate of sulfur dioxide in corn grain followed first-order kinetics, with rate constants in the range 1.49×10-7to 9.78×10-7s-1for steeping temperatures from 25 to 55 °C. The Arrhenius activation energy for sulfur dioxide loss was 60.5 kJ/mol. The fitting of the mathematical model to the absorption curves determined the diffusion coefficient of sulfur dioxide in corn kernels. These varied from 1.17×10-11to 5.18×10-11m2/s for the temperature range 25-55 °C. Temperature-dependent diffusion coefficients was shown to obey the Arrhenius equation with an activation energy of 39.8 kJ/mol.